Coopetition Strategy—What is in It for All?: A Study of Common Benefits in the Polish Energy Balancing Market. Issue 2 (2nd April 2016) - Czakon, Wojciech; Mucha-Kuś, Karolina; Sołtysik, Maciej
Abstract: Coopetition is an increasingly established concept in the literature, with a growing number of empirical works detailing it many facets, results, and nature. Prior research adopts mainly an individual level of analysis, focusing on private benefits. Studies at the collective level of analysis, exploring common benefits arising from coopetition, remain very rare. We address this gap by studying the contribution of coopetition to common benefit generation in the Polish energy balancing market. Our evidence suggests that the more the 31 megastores in Poland coopete, the lower the energy balancing costs they are able to achieve.